Influence assessment of a campaign to encourage the reduction of water consumption - Silva, Daniela Lima (Revista Hipótese, 2015)
This research, which was developed between 2012 and 2014 as dissertation and aims to analyze the influence of a campaign to encourage the reduction of water consumption which was held with a group of condominiums in the city of São Paulo. For this analysis we prepared a proposal for treatment of water consumption data of the participants condominiums, using descriptive statistics and time-series forecasting models (forecasting). Also, the temperature variation was analyzed in this period and exerted some influence on consumption of water, using inferential statistics (correlation and regression). In addition, a group of condos that did not participate in the campaign was adopted as a control framework. After analysis, it was found that the campaign did not influence significantly the water consumption reduction and there was also no correlation between water consumption and temperature variations during the period.
Keywords: Water consumption; consumption data analysis; descriptive statistics; time series